2021
DOI: 10.3390/jpm11070651
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Soluble LAG3 and Soluble Immune Checkpoints Profile in Advanced Head and Neck Cancer: A Pilot Study

Abstract: Unresectable recurrent and/or metastatic head and neck squamous cell carcinoma (R/M HNSCC) has a very poor prognosis. Soluble immune checkpoints (sICs) are circulating proteins that result from the alternative splicing of membrane proteins and can modulate the immune response to cancer cells. The aim of our pilot study was to determine the possible role of a comprehensive evaluation of sICs in the classification of prognosis and response to treatment in patients with advanced disease. We evaluated several sICs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
(40 reference statements)
1
29
0
Order By: Relevance
“…The LAG3 expression level can be a marker of poor prognosis in various tumors. In NSCLC and advanced CRC, the high expression of FGL1 and LAG3 are related to the poor 5-year OS, respectively ( 43 , 85 ), high level of soluble LAG3(>377pg/ml) predicts unfavorable PFS and OS in HNSCC ( 86 ). More LAG3 + cells induce the immunosuppressive microenvironment and predict the poor prognosis, in EBV-positive and MLH1-defective gastric cancer, high infiltration of LAG3 + cells may induce immune escape in tumors with fewer IFN-γ + cells and perforin-1 + cells and more Treg cells and M2 macrophages in this subtype of gastric cancer ( 87 ), similar results can be found in MIBC and pancreatic ductal adenocarcinoma ( 56 , 88 ).…”
Section: Clinical Application Of Lag3/fglmentioning
confidence: 99%
“…The LAG3 expression level can be a marker of poor prognosis in various tumors. In NSCLC and advanced CRC, the high expression of FGL1 and LAG3 are related to the poor 5-year OS, respectively ( 43 , 85 ), high level of soluble LAG3(>377pg/ml) predicts unfavorable PFS and OS in HNSCC ( 86 ). More LAG3 + cells induce the immunosuppressive microenvironment and predict the poor prognosis, in EBV-positive and MLH1-defective gastric cancer, high infiltration of LAG3 + cells may induce immune escape in tumors with fewer IFN-γ + cells and perforin-1 + cells and more Treg cells and M2 macrophages in this subtype of gastric cancer ( 87 ), similar results can be found in MIBC and pancreatic ductal adenocarcinoma ( 56 , 88 ).…”
Section: Clinical Application Of Lag3/fglmentioning
confidence: 99%
“…LAG-3 cleavage by ADAM10 and ADAM17 produces sLAG-3, which alleviates T cell inhibition; [11] positively regulates CD8+ T cells, interleukin (IL)-12, IFN-g, and dendritic cells (DCs); and functions as a prognostic marker in multiple cancers. [15,[40][41][42][43] Collectively, these results show that LAG-3 expression is regulated through multiple mechanisms, including at the epigenetic, transcriptional, post-transcriptional, and posttranslational levels. Agents targeting LAG-3 regulators may contribute to novel combination immunotherapy treatment strategies in cancers.…”
Section: Structure and Ligands Of Lag-3mentioning
confidence: 80%
“…[94,95] Moreover, high baseline sLAG-3 was associated with poorer PFS in HNSCC patients receiving ICIs or chemotherapy. [41] A mutation in the LAG-3 gene, preventing cleavage by ADAM-10/17, led to elevated levels of LAG-3, which may be a mechanism of resistance to ICIs. [96] Higher LAG-3 expression in tumor tissues is related to an adverse prognosis in most types of cancer, including pancreatic cancer, [97] high-grade soft-tissue sarcoma, [98] salivary gland carcinomas, [99] clear cell renal cell carcinoma, [100] HNSCC, [101] esophageal squamous cell carcino-ma, [52] and oral squamous cell carcinoma.…”
Section: Correlation Between Lag-3 and Efficacy And Prognosis In Cancersmentioning
confidence: 99%
“…In NSCLC, low serum LAG-3 expression was associated with advanced or metastatic disease (36). On the contrary, high levels of soluble LAG-3 were association with poor PFS and OS in advanced head and neck cancer (37). These data suggested that further investigation of the prognostic and predictive roles of serum LAG-3 in other types of cancer is required.…”
Section: Discussionmentioning
confidence: 99%